Снежная королева - Андерсен Ханс Кристиан (Серия "Почитай мне сказку", 2021)
Печатается в сокращении Экземпляры: ф13; ф14; ф15; ф16; ф17 (20211216) / Инвентарный номер: 62164 / Цена: 16.00 / Сис.шифр: Д / Авт.знак: А 65 / ГРНТИ: 17.82.93 / ББК: 84(4Дан)